KONTRIBUSI PENGETAHUAN METAKOGNITIF DAN REGULASI METAKOGNITIF TERHADAP KEMAMPUAN BERPIKIR ILMIAH MAHASISWA IAKN KUPANG - Oemanu, Jelia. B. A.; Ali, Umar; Syahputra, Andrian Wira (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Scientific thinking skills becomes a important competency for a student in achieving a successful learning process. The success of students in their learning process is influenced by their own ability to process their thinking processes or what is often called metacognition. Several studies on metacognition have been conducted but only associated with academic achievement and critical thinking skills and are more likely to be directed at the exact sciences. Likewise with research on scientific thinking, only limited to the cognitive level and has not yet touched on the metacognition dimension. Based on this background, the purpose of this research is to analyze the contribution of metacognitive knowledge and metacognitive regulation to the scientific thinking skills. The research method is a quantitative method with the type of ex post facto. The data collection technique used an instrument in the form of questionnaire with a sample of 194 students who were actively registered in the Christian Religious Education study program at Kupang State Institute of Christianity. The data analysis technique used is multiple regression analysis. The result showed that there was a contribution of metacognitive knowledge to the scientific thinking skills by 21,6%. Meanwhile, the contribution of metacognitive regulation to the scientific thinking skills by 0,9% and the contribution of metacognitive knowledge and metacognition regulation to the scientific thinking skills by 22,5%. The rest, 77,5% of scientific thinking skills is determined by other factors such as motivation, level of critical thinking, self monitoring, and various other aspects of factors.